2009
DOI: 10.1016/j.ejvs.2008.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Complex Aneurysmal Disease with Fenestrated and Branched Stent Grafts

Abstract: In selected patients, fenestrated and branched stents appear to be a safe and effective alternative to surgery for juxtarenal and thoracoabdominal aneurysms. The complication and mortality rates are low. The long-term durability of this procedure, however, needs to be proven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…Many patients can avail the facility of endovascular repair, with the increase in the availability of these types of devices [16][17][18]. The speed and the level of quality that will be attained will depend not only on aggressively pursuing new ideas, but also on cooperation and support from industry [11,19].…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Many patients can avail the facility of endovascular repair, with the increase in the availability of these types of devices [16][17][18]. The speed and the level of quality that will be attained will depend not only on aggressively pursuing new ideas, but also on cooperation and support from industry [11,19].…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Unlike fenestrated stent grafts 13–15 and modular branched stent grafts, 9,10 the integrated stent graft we designed was implanted as a whole entity, with the branches already attached to its main body, and the deployment and release of the integrated stent graft were accomplished in one step. This integrated configuration can minimise the risk of the disintegration 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Some centers have used branched devices exclusively while others have used fenestrations routinely. [16][17][18] Others utilize devices with a combination of branches and fenestrations. Published series have shown that fenestrations have an extremely high patency in the renal arteries while longer branches tend to kink over time as the aneurysm sac shrinks.…”
Section: N Discussionmentioning
confidence: 99%